Applications and metrology at nanometer scale. - Dahoo, Pierre Richard (Mechanical engineering and solid mechanics series., 2021)
To develop innovations in quantum engineering and nanosystems, designers need to adopt the expertise that has been developed in research laboratories. This requires a thorough understanding of the experimental measurement techniques and theoretical models, based on the principles of quantum mechanics. This book presents experimental methods enabling the development and characterization of materials at the nanometer scale, based on practical engineering cases, such as 5G and the interference of polarized light when applied for electromagnetic waves. Using the example of electromechanical, multi-physical coupling in piezoelectric systems, smart materials technology is discussed, with an emphasis on scale reduction and mechanical engineering applications. Statistical analysis methods are presented in terms of their usefulness in systems engineering for experimentation, characterization or design, since safety factors and the most advanced reliability calculation techniques are included from the outset. This book provides valuable support for teachers and researchers but is also intended for engineering students, working engineers and Master's students.